1997
DOI: 10.1093/ejo/19.6.657
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes of the TMJ condyles of 100 patients treated with the Herbst appliance in the period of puberty to adulthood: A long-term radiographic study

Abstract: SUMMARY One hundred consecutive patients were treated with the Herbst appliance in the period of puberty to adulthood. The orthopaedic effects on the morphology of the condyles were described from orthopantomographic and transpharyngeal radiographs. The orthopaedic treatment effect was, in most cases, visible as a change in morphology of the condyle, a double contour in the distocranial part of the condyle and sometimes also at the distal surface of the ramus. In patients at the peak of puberty, the double con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1
10

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 25 publications
2
34
1
10
Order By: Relevance
“…Our results are in agreement with a study that found a decreased prevalence of structural bone changes during treatment with the Herbst appliance (9), probably due to remodeling (6)(7)(8)(9). In contrast, the left condyle in case 26 had osteophytes (DBD) associated with ALDD and a non-biconcave shape of the disc at T 1 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are in agreement with a study that found a decreased prevalence of structural bone changes during treatment with the Herbst appliance (9), probably due to remodeling (6)(7)(8)(9). In contrast, the left condyle in case 26 had osteophytes (DBD) associated with ALDD and a non-biconcave shape of the disc at T 1 .…”
Section: Discussionsupporting
confidence: 93%
“…Class II malocclusion associated with mandibular retrognathism may be treated using orthopedic functional appliances in the first phase of treatment to advance the mandible and to improve its anteroposterior adjustment during growth (1)(2)(3)(4)(5)(6)(7)(8)(9). In the second phase of treatment, fixed orthodontic appliances are used to refine occlusion (1,9).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations